Rehabilitation Science in Context (Clinical and Experimental Biomedicine,, 2018)
The focus of this book lies on novel aspects of rehabilitation medicine used as a treatment tool in both physical and mental spheres. The articles cover a diverse spectrum, such as rehabilitation in orthopedic pathologies, the exemplary of which is knee joint degeneration, in perioperative metastatic cancer diseases, or in neural degeneration requiring a transplant of donor nerve fibers into the defunct nerve. Advanced research studies involving proprioceptive neuromuscular facilitation, photobiomodulation, or yoga meditative techniques to regain functional ability are dealt with. The topic is expanded by a comprehensive picture of chosen molecular, genetically underpinned, diagnostics in hepatitis C infections and of novel ideas in drug design holding a curative promise in central neurodegeneration, such as development of brain-blood-barrier permeable oleic derivatives of the hydrophilic dopamine compound. The emerging rehabilitative modes and applications are posed to influence future health care delivery. The state-of-the art research is addressed to scientists, clinicians, therapists, and allied health care professionals. .